Typology and Characteristics of Community-Based Waste Banks in Integrated Agricultural Waste Management Systems in Ciamis Regency : Tipologi dan Karakteristik Bank Sampah dalam Sistem Pengelolaan Sampah Berkelanjutan Berbasis Masyarakat Terintegrasi Agrikultur di Kabupaten Ciamis - Bagus Martiandi; Sambas Basuni; Soeryo Adiwibowo (Universitas Muhammadiyah Palembang, 2025)
Waste management is a major challenge for sustainable development in Indonesia, where 40.26% of Indonesia’s waste remains unmanaged. Waste banks have emerged as innovative community-based solution that combines waste reduction with socio-economic benefits and agriculture for community. This study aims to identify and analyze the typology and characteristics of waste banks in Ciamis Regency and evaluate their effectiveness in supporting integrated agricultural sustainable waste management systems. The research method uses a qualitative approach with an instrumental case study design on three waste bank units: Main Waste Bank (MWB) Ciamis, Unit Waste Bank (USB) Al Huda, and BSU Tumras. Data were collected through in-depth interviews and closed interviews with 18 respondents, participatory observation, and documentation studies. Data analysis used descriptive and taxonomic analysis methods.The research results show three main typologies of waste banks in Ciamis Regency: Type A (Large Scale) with a volume >10 tons/month that acts as a strategic coordinator; Type B (Medium Scale) with a volume 1,834.74 kg/month that acts as a coordination-implementation bridge; and Type C (Small Scale) with a volume 443.1 kg/month month that focuses on direct community service. Each typology shows different effectiveness: BSI Ciamis 85%, BSU Al Huda 78% (15% agricultural itegration), and BSU Tumras 70% (12% agricultural integration). The waste bank system in Ciamis Regency has successfully reduced 15% of waste generation to landfills and increased the recycling rate from 25% to 60%, and produced 150 kg/month of organic fertilizer and animal feed support local food security. This study concludes that the diversity of waste bank typologies reflects adaptation to local conditions and contributes to the effectiveness of integrated community-based agricultural sustainable waste management systems.